Judicial Review of Hospitals' Legal Responsibility of Patients' Rights After the Covid-19 Pandemic - Irawati, Jovita (Law Review, 2023)
Normatively, the legal responsibilities of hospitals in fulfilling patient rights are stipulated in the Health Act, the Hospital Act, and the Medical Practice Act. During the Covid-19 pandemic, which was declared a health emergency, various statutory provisions were also enacted, such as Infectious Disease Outbreak Law, Health Quarantine Law, Presidential Decree Number 11 of 2020 concerning the Determination of the National Public Health Emergency of Corona Virus Disease 2019 (Covid-19) and Minister of Health Regulation Number 4 of 2018 concerning Hospital Obligations and Patient Obligations. In practice, the increasing number of Covid-19 cases in Indonesia has resulted in hospitals being unable to accommodate patients who need treatment, especially patients with severe and critical conditions who require ICU treatment rooms. This study aims to find out hospital’s legal responsibility after the Covid-19 pandemic, especially for the protection of patient’s medical record security under the scheme of telemedicine services. In terms of facilities and infrastructure, the government needs to provide support by increasing the number of emergency hospitals to accommodate patients. This study uses normative juridical research methods supported by empirical studies. The results show that despite limitations in providing excellent health services to patients, hospitals must still maintain the rights of patient’s medical record security and safety while undergoing hospitalization. Legal umbrella is neeeded to guarantee the rights of health workers and hospitals in providing services to patients during this pandemic, especially the protection of Occupational Health and labor social security norms.